PENGARUH PIJAT AKUPRESURE TERHADAP EMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER I DI PMB NIYET - Heni Heri Yeni; Rizki Natia Wiji (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2023)
The incidence rate of emesis gravidarum is more than 80% in pregnant women in Indonesia experiencing excessive nausea and vomiting. The incidence of cases of emesis gravidarum is 8 to 32 cases per 1,000 pregnancies. Therefore, handling nausea and vomiting in pregnancy really needs to be done. Purpose: The effect of acupressure massage for pregnant women in the first trimester the incidence of emesis gravidarum. Methods: This research is a quantitative study with quasi-experimental research design, The study design was the One Group Pre Test Post Test to determine the effect before and after being given acupressure massage. Conclusion:. Statistical test results showed that the average value of the variable frequency of nausea and vomiting before being given acupressure massage was 5.00 with standard deviation of 0.871 and the average value after being given acupressure massage was 2.43 with a standard deviation of 0.728. The difference between the frequency of nausea and vomiting before and after being given was 2.57 and a value of p = 0.000 (<0.005) was obtained, which means that there was a significant difference in the average frequency of nausea and vomiting in pregnant women in the first trimester before and after being given acupressure massage. The results of information about initial treatment for pregnant women who experience emesis gravidarum using acupressure massage at point P6 which is on 3 fingers below the wrist. Besides being practical, acupressure massage can be done wherever pregnant women are either when they are active or when they are resting.